Modeling method for grounded coplanar waveguide with vector fitting technique. Issue 5 (11th March 2022) - Tan, Daidao; Lu, Hongliang; Zhao, Ranran; Qi, Junjun; Zhang, Yimen; Zhang, Yuming; Cheng, Wei
Abstract: In this article, a semiempirical equivalent circuit model of the grounded coplanar waveguide (GCPW) based on the vector fitting is proposed for the first time, which improves the accuracy in high frequency. It offers an effective solution for the millimeter GCPW modeling. This model takes into account nonideal effects such as skin effect and substrate coupling effect, which realizes the combination of numerical method and physical meaning. The method we propose aims to use sequential quadratic programming algorithm to solve strictly passive problems. Good agreement is obtained between the modeled and measured data up to 40 GHz.